Impact of physical distance on student’s internship and employment opportunity during Covid-19 pandemic in Malaysia - Haque, A. K. M. Ahasanul; Abd Manaf, Noor Hazilah; Sarker, Md Atiqur Rahman; Kabir, Sardar Md Humayun (Faculty of Law, UiTM, 2021)
Physical distance is essential during COVID-19 pandemic as one of the protective measures. Many organizations around the world are advising their employees to work from home. However, final year students are deprived of getting work experience before they graduate due to this pandemic. Internship program for students require hands on training and face-to-face office work, which is not possible at this moment. Besides, many graduating students are facing challenges to secure an entry-level job. Since, the spread of Corona virus is increasing in Malaysia, Movement Control Order (MCO) is imposed more frequently. As a result, many businesses are affecting with financial performance and the number of new hiring has drastically reduced in Malaysia. Thus, students in Malaysia are facing challenge to find internship, which is part of their degree requirements. Besides, their employment opportunity is almost uncertain. This study is qualitative in nature, and the findings of the study have been investigated through six in-depth interviews and one Focus Group Discussion conducted on final year university students in Malaysia. This study discusses the legal rights of the student for their access to education and employment right, which will draw the attention of employers, policy makers and educational institutions for further actions to be taken.